The Impact of Risk Disclosure Tone and Institutional Ownership on Firm Value - Ningrum, Wulan Kesuma; Helmy, Herlina (Universitas Negeri Padang, 2024)
Purpose – This study aims to examine the impact of risk disclosure tone and institutional ownership on firm value in manufacturing companies within the food & beverage and chemical subsectors listed on the Indonesia Stock Exchange for the period 2020-2022.Design/methodology/approach – This study is a causal research utilizing a quantitative approach. The population for this research includes all manufacturing companies in the food & beverage and chemical subsectors listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The sampling method employed is purposive sampling.Findings – The results of this study find that the tone of risk disclosure and institutional ownership have no effect on firm value.Originality/value – This study provides a novel contribution to the literature on the tone of risk disclosure and institutional ownership in relation to firm value. First, it enriches the existing literature on the tone of risk disclosure, which remains limited in emerging markets, particularly in Indonesia, by utilizing a measurement approach that differs from similar studies. Second, this research broadens the examination of institutional ownership, which has been widely studied but has produced diverse results.Research limitations/implications – The results of this study indicate that the tone of risk disclosure and institutional ownership do not affect firm value. The limited generalizability of the sample and research period in this study may provide an opportunity for further research. Future studies could explore a broader range of industries, longer time periods, or different geographic regions to enhance the generalizability of the findings and provide deeper insights into the relationship between these factors and firm value.